ANALISIS KEMAMPUAN PEMAHAMAN MATEMATIS SISWA DENGAN MENGGUNAKAN PENDEKATAN PMRI - Anesty G Hutajulu; Eunike Kantu; Navel Mangelep (Universitas Nias Raya, 2026)
This study aims to analyze students’ mathematical understanding through the implementation of the Indonesian Realistic Mathematics Education (PMRI) approach. The background of this research focuses on the still low ability of students to comprehend mathematical concepts deeply, particularly in connecting representations, interpreting information, and applying concepts in contextual situations. The PMRI approach was chosen because it emphasizes the use of real contexts and modeling processes, allowing students to construct their own understanding. This study employed a qualitative descriptive method with secondary school students as subjects. Data were collected through mathematical understanding tests, classroom observations, and interviews. The understanding indicators analyzed included the ability to restate concepts, provide examples and non-examples, connect concepts, represent situations in mathematical models, and apply concepts in problem-solving. The results show that PMRI-based learning helps students achieve more meaningful understanding of concepts. Real-world contexts facilitate students’ initiation of the thinking process, while discussion and modeling activities support the development of more mature mathematical representations. However, some students still experienced difficulties at the stages of abstraction and generalization of concepts.